TERAPI EYE MOVEMENT DESENSITIZATION AND REPROCESSING TERHADAP TINGKAT STRES PASIEN DIABETES MELITUS - Gita Paramita; Wayan Candra; IGA Harini (Jurnal Gema Keperawatan, 2019)
This study aims was to identify stress levels before and after EMDR therapy and analyzing the effect of EMDR therapy on stress levels in diabetes mellitus patients at Puskesmas Tegallalang II on 2019. The design of this study was preexperimental with a one-group pre-post test design. Samples were taken by purposive sampling method with a sample of 17 peoples. Stress level collection instrument using PSS. The results showed that from 17 samples before EMDR therapy the range of stress included mild, moderate and severe stress, where the most respondents had moderate stress which is 12 peoples (70.6%), after being given EMDR therapy the range of the stress level of the subject was mild stress and moderate stress. EMDR was significantly effected stress level on diabetes mellitus patient with a p value = 0.002 (alpha = 0.05) which could mean that EMDR therapy could reduce stress levels in diabetes mellitus patients.